Cultural Participation, Social Media Affect and Art - Stage, Carsten; Eriksson, Birgit; Møhring Reestorff, Camilla (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This special issue of Conjunctions brings together seven academic articles that shed light on to two different fields: the affective and bodily dimension of social media participation and cultural participation in aesthetic activities, in- or outside institutions. The articles more specifically present new research from a range of national and global contexts on the participatory cultures related to faketuality, Hilary-hating, feminist podcasts, Zentrum Für Politische Schönheit, social art, art and cultural policy and youth participation in cultural institutions. The issue ends with a review of Nico Carpentier’s book The Discursive-Material Knot.